2021
DOI: 10.1136/bmjdrc-2021-002162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring support needs of people living with diabetes during the coronavirus COVID-19 pandemic: insights from a UK survey

Abstract: IntroductionThe coronavirus COVID-19 pandemic has radically compromised healthcare for people living with chronic conditions such as diabetes. Government-imposed restrictions to contain the spread of the virus have forced people to suddenly adjust their lifestyle. This study aimed to capture the impact of the pandemic on people living with diabetes and the views of these individuals on ways in which the information, advice and support they are receiving could be improved.Research design and methodsAn online an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…A total of 20 studies reported on PA during the pandemic [ 18 , 20 , 24 , 26 - 29 , 33 - 45 ], and 35% (7/20) of these studies [ 28 , 33 , 38 , 40 - 43 ] reported on continual or increase in PA among the participants in their studies. Disruptions in routines, fear of going outdoors, lack of motivation, as well as increased anxiety and stress during COVID-19 led to the decline in PA in 65% (13/20) of these studies [ 18 , 20 , 24 , 26 , 27 , 29 , 34 - 37 , 39 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 20 studies reported on PA during the pandemic [ 18 , 20 , 24 , 26 - 29 , 33 - 45 ], and 35% (7/20) of these studies [ 28 , 33 , 38 , 40 - 43 ] reported on continual or increase in PA among the participants in their studies. Disruptions in routines, fear of going outdoors, lack of motivation, as well as increased anxiety and stress during COVID-19 led to the decline in PA in 65% (13/20) of these studies [ 18 , 20 , 24 , 26 , 27 , 29 , 34 - 37 , 39 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 studies reported on dietary habits during the pandemic [ 18 - 20 , 24 , 27 , 29 , 30 , 33 , 35 , 37 , 38 , 41 , 45 , 46 ], and 50% (7/14) of these studies [ 19 , 20 , 33 , 37 , 38 , 41 , 46 ] reported improved diet management among their participants. Reasons were of increased time availability, with more meals being prepared at home and lockdown restrictions limiting takeaway consumptions among participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations